Unveiling the Drivers of Economic Growth in Somalia: The Role of Energy Consumption, Environmental Pollution, and Globalization - Hussein, Hassan Abdikadir; Warsame, Abdimalik Ali; Ahmed, Mohamed Yusuf; Salad, Mohamed Ahmed (International Journal of Energy Economics and Policy, 2024)
The fundamental goal of economic policy in most countries around the world is to achieve sustainable economic growth. Energy serves a crucial role in fostering sustainable economic growth in both developing and developed nations. Hence, the study aims to explore the impact of energy consumption, environmental pollution, and globalization on economic growth in Somalia using data from 1990 to 2020 for all variables. The study employs the autoregressive distributed lag (ARDL) bound test. The empirical results of the bound test indicate that energy consumption and globalization are statistically significant and have a positive effect on economic growth. In addition, environmental pollution has a negative impact on economic growth in Somalia. Moreover, the findings revealed that energy consumption and globalization promote economic growth. while environmental pollution harms economic growth in Somalia. Based on the empirical evidence, the study provides several policy implications.